Retention of tocilizumab and anti-tumour necrosis factor drugs in the treatment of rheumatoid arthritis. (August 2013) - Hishitani, Y; Ogata, A; Shima, Y; Hirano, T; Ebina, K; Kunugiza, Y; Shi, K; Narazaki, M; Hagihara, K; Tomita, T; Yoshikawa, H; Tanaka, T; et al.
<x xml:space="preserve">Abstract</x> Objectives: The retention of the anti-rheumatic agent tocilizumab (TCZ) has not been well documented in patients with rheumatoid arthritis (RA). We conducted an observational study to compare the retention of TCZ and anti-tumour necrosis factor (TNF) drugs in the treatment of patients with RA. Method: We reviewed continuation rates and causes of discontinuation of biological agents (biologics) by assessing medical records of patients with RA who were administered biologics at our institute from September 1999 to April 2012, using the Osaka University Biologics for Rheumatic Diseases (BiRD) registry. Results: A total of 401 patients were included. TCZ, infliximab (IFX), etanercept (ETN), and adalimumab (ADA) were administered to 97, 103, 143, and 58 patients, respectively. There were some differences between the baseline characteristics of the groups. The median duration (range) of TCZ, IFX, ETN, and ADA administration was 2.5 (0.1–12.6), 1.9 (0.0–7.7), 2.9 (0.0–11.3), and 1.3 (0.0–3.4) years, respectively. Continuation rates for TCZ and ETN were significantly higher than those for IFX and ADA. Multivariate analyses showed that discontinuation due to lack or loss of efficacy was significantly less common in the TCZ group than in the other groups. Discontinuation due to overall adverse events was not significantly different between treatment groups. Conclusion: TCZ and ETN show better retention than IFX or ADA in the treatment of RA.